METHODOLOGICAL SIGNIFICANCE OF THE CHARACTERISTICS OF HUMAN NATURE FOR THE FORMATION OF THE VIRTUAL LEARNING ENVIRONMENT - Irina Andreevna Svintorzhitskaya (Современная наука и инновации, 2022)
The article considers the methodological significance of the entities of the characteristics of human nature for the analysis of the role of virtual technologies of University training system as part of the multimedia symbolic environment.